Digital design theory readings from the field - Armstrong, Helen (Design Briefs, 2016)
Digital Design Theory bridges the gap between the discourse of print design and interactive experience by examining the impact of computation on the field of design. As graphic design moves from the creation of closed, static objects to the development of open, interactive frameworks, designers seek to understand their own rapidly shifting profession. Helen Armstrong's carefully curated introduction to groundbreaking primary texts, from the 1960s to the present, provides the background necessary for an understanding of digital design vocabulary and thought.Accessible essays from designers and programmers are by influential figures such as Ladislav Sutnar, Bruno Munari, Wim Crouwel, Sol LeWitt, Muriel Cooper, Zuzana Licko, Rudy VanderLans, John Maeda, Paola Antonelli, Luna Maurer, and Keetra Dean Dixon. Their topics range from graphic design's fascination with programmatic design, to early strivings for an authentic digital aesthetic, to the move from object-based design and to experience-based design. Accompanying commentary assesses the relevance of each excerpt to the working and intellectual life of designers.